Intraoperative defibrillation testing during replacements of implantable cardioverter-defibrillators: The Simpler trial. (19th May 2022) - Milman, A; Nof, E; Beinart, R; Regev, E; Rav Acha, M; Kutyifa, V; Merkely, B; Biffi, M; Cha, YM; Ovdat, T; Klempfner, R; Glikson, M
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Maurice Kahn Foundation via the Mayo- Sheba Collaboration Fund. Background: The need for intraoperative defibrillation testing (DFT) during implant and/or replacement of implantable cardioverter-defibrillators (ICDs) has been a matter of debate for many years. This debate was put to rest by the Simple and the Nordic ICD trials, and the practice of testing during new implantations has practically been nearly abandoned. Nevertheless, induction of VF for testing purposes (VFT) may still have an important role in selective populations at risk for defibrillation failure, who were not included in the SIMPLE and Nordic trials. One such population includes those who undergo device replacements. Old registries demonstrated an increased incidence of significant findings in VFT during replacements. In the present study, we sought to test this observation. Objectives: Evaluate frequency of significant findings and the safety of VFT in subjects undergoing device replacement. Methods: A prospective observational multi-center study of VFT included consecutive patients undergoing ICD generator replacement in 5 centers in Israel, Europe, and the US. All centers followed the same VFT protocol. The primary outcome was defined as failure to terminate induced VF with a single shock at 10 Joules below the maximal capacity of the device. Secondary outcomes included complications of VFT. Patients were followed-up at 1 month and 6 months post-procedure. Data collection included documentation of any peri-operative complications and clinical endpoints (occurrence of appropriate shock, inappropriate shocks, lead failure, need for re-intervention, and infection). Results: A total of 92 patients were eligible, and consented for the study, of which 84 underwent DFT during battery replacement. The median age was 68 years and 79.8% were male subjects. Induction of VF was successful in all 84 patients as well as VFT with a successful conversion on first attempt. During follow up one patient had two appropriate ICD shock events. In four patients, the ICD programming was changed. None suffered an inappropriate shock. There was no evidence of lead malfunction. A total of two deaths occurred, none of which were related to the device. Conclusion: The present study found VFT was not associated with complications in patients undergoing ICD/CRTD generator replacement but produced no clinically important information.